Martensitic precipitation in AISI 304 stainless steels - stress corrosion - Dionicio Padilla, Eusebio (2002)
The research project: Martensitic precipitation in AISI 304 stainless steel-corrosion cracking has determined that the material tested under different compressive loads, the austenite phase producing deformed martensite phase, which is magnetic. The accelerated corrosion test deformed martensite material having a solution of magnesium chloride in boiling 42% produces a type of corrosion transgranular.